Effect of the Employed Material Model on the Predicted Behaviour of Corrugated Metal Pipes. Issue 10 (October 2021) - El Naggar, Hany; Campbell, Alex; Ezzeldin, Islam
In recent years, two-dimensional (2D) finite element modeling (FEM) has been used to explore how the structural integrity of a corrugated metal pipe (CMP) culvert is affected by simulation of its constituent components (i.e., the pipe metal, surrounding soil, or both). However, under various conditions, the nature of the problem is three-dimensional (3D) and 2D simulations may fall short of producing reasonable predictions. In this paper, the effect of various loading types on the structural response of round CMP culverts is investigated using 3D finite element (FE) models. The validity of the model was assessed by comparing the model output with previously published results from full-scale laboratory testing. The mechanical behaviour of real soil involves a significant degree of non-linearity. In soil-structure interaction problems such as the one considered here, it seems reasonable to expect that the non-linear behaviour of the soil, together with that of the soil-structure interface, would have a significant effect on the response of the structure. Furthermore, 2D models are limited in their ability to account for certain aspects of the actual, 3D problem. Such aspects include surface live load spreading through the cover soil and the structural behaviour of a corrugated pipe. This paper details the development of a comprehensive, 3D, non-linear FE model capable of simulating the behaviour of intact CMP culverts under backfilling and live loading. The analysis showed that the hyperbolic strain hardening model produced predicted response of the culvert that is very close to the obtained experimental data. However, the numerical results obtained using the Mohr-Coulomb or the linear elastic soil models were of less accuracy.